Peran Komunikasi Lembaga Masyarakat dalam Mengatasi Non-Consensual Dissemination of Intimate Images (NCII) di Indonesia - Ariel Syalia Prananda; Shafa Ayu Aurellia; Wahidah Mevi Nihayah; Talitha Vanya Ekta; Bunga Cinta Ariesa; Ibtisam Mumtaz Khairunnisa; Rani Sukma Ayu Suteja (Jurnal Media dan Komunikasi Indonesia, 2023)
NCII stands for Non-Consensual Dissemination of Intimate Images. This term describes the dissemination of intimate content, whether in the form of photos or videos, which is carried out without the consent of the parties involved in the content. NCII is a problem that deserves serious attention in nowadays life. Even though indirectly there is a law to take action against NCII perpetrators, in reality legal protection alone is not enough to overcome NCII problems. It needs communication strategies and involvement from various community institutions in preventing the occurrence of NCII, because after all preventive measures would be much better. Communication includes strategic efforts through socialization, education, advocacy, and mentoring in order to increase awareness of the use of information technology, so as to avoid NCII, one of which is through increasing digital literacy. Therefore, through this conceptual article, the author tries to describe how the role of communication from institutions in society can prevent the occurrence of NCII, including the role of institutions and legal regulations, the role of educational institutions, the role of community organizations, the role of the mass media, and the role of individuals in using communication technology. The data collection comes from observing phenomena and studying literature in order to get relevant references. The conclusion of this article is that the NCII case is not the responsibility of just one person. Synergy between various elements of society is important in creating a safe environment from NCII's actions and supportive situation for victims.